Can Elevated IGF‐1 Levels Among Patients With Ehlers–Danlos Syndrome Cause Idiopathic Intracranial Hypertension?. Issue 10 (29th October 2013) - Kurian, Michelle; Solomon, Glen D.
<x xml:space="preserve">Abstract</x> We offer for consideration a possible association between hypermobility syndrome seen in Ehlers–Danlos syndrome and risk of potential development of idiopathic intracranial hypertension – mediated primarily through the effects of insulin‐like growth factor‐1.